Caracterização de trigo sintético à giberela (gibberella zeae) (schw.) petch, índice meiótico e diversidade genética - Frizon, Patrícia (2015)
This study had the purpose to characterize twenty accessions of synthetic wheats, from the crossing of Triticum durum (AABB genomes) x Aegilops tauschii (genome DD) for resistance to Fusarium head blight. These were compared with six cultivars of wheat (AABBCCDD Genomes), with different levels of resistance through phytopathological, cytogenetic and molecular analysis. The design was randomized blocks, with twenty six treatments and three replications. In silking, grain perithecia of Gibberella zeae were distributed on the soil surface. At the harvest point, fifty dried ears of wheats, uniform in size, were harvested and threshed. The incidence of FHB was assessed by the percentage of grains with symptoms. The data were submitted to analysis of variance and means were compared by the Scott and Knott test at 5% probability. For the analysis of genetic stability, five spikes per genotype at the stadium ten Feeks & Large scale were collected and fixed in Carnoy solution. The cytological slides were prepared by soaking method and the coloration of cells was done with 1% acetic carmine. Observations were under an optical microscope, analyzing the presence and absence of micronuclei in tetrad stage being made of the normal tetrads and micronucleus counts for subsequent meiotic index calculation. Genotypes were considered meiotic stable when the meiotic index was above 90%. For the molecular analysis of the twenty six DNAs extracted from wheat genotypes and over 42 microsatellite markers for the creation of genetic diversity study were used. Regarding the reaction to FHB, the best results were obtained with CIGM93.298 and CIGM92.1666 accesses, in 2014 and 2015, respectively. These accessions were meiotic stable, as presented meiotic index greater than 90% in two years. In genetic dissimilarity, synthetic wheats showed high diversity. A total of 73 alleles were detected by these markers, with the maximum of four alleles per locus. The polymorphism information content, showed that genome B is greater genetic diversity between the genomes B and D of synthetic hexaploid wheats. The results indicated that the synthetic hexaploid wheat is excellent germplasm for gene introgression lines and in wheat cultivars.